Accelerating Gifted Students in Canada: Policies and Possibilities - Kanevsky, Lannie; Clelland, Debbie (Canadian Journal of Education/Revue canadienne de l'éducation, 2014)
Policy documents related to gifted education and 18 forms of accelerated learning were collected from all Canadian provinces and territories.  The contents of 69 documents were examined to determine the nature and extent of support for services to gifted students in general, as well as acceleration. The results provide a sense of the variability and flexibility of these policies across Canadian jurisdictions.  Documents from Alberta, BC, New Brunswick and Nova Scotia provided the greatest explicit support for advanced learners.  Content-based forms of acceleration (e.g., credit by examination and subject acceleration) were more often supported than grade-based (e.g., grade skipping and early entrance to Kindergarten).